Intracellular DNA sensing pathways - Hornung, Veit (Henry Stewart Talks, 2012)
Mechanisms of intracellular DNA sensing, Intracellular DNA sensing that results in inflammasome activation, DNA sensing mechanisms leading to pro-inflammatory gene expression